THE USE OF CADENCE AND RHYTHM IN PROSE: THE EXAMPLE OF MOBY-DICK BY HERMAN MELVILLE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article explores how Herman Melville uses cadence and rhythm in Moby-Dick to elevate the novel's prose and deepen its thematic resonance. It begins by defining cadence as the flow and modulation of words and rhythm as the pattern of stresses and pauses, emphasizing how Melville employs these tools to create a text that feels alive and immersive. The article highlights the brevity of the opening line, “Call me Ishmael,” as an example of simple yet striking rhythm, which contrasts with the sprawling, wave-like sentences that dominate much of the novel. Melville’s rhythm adapts to the mood of each scene, moving from the slow, hypnotic cadence of Ishmael’s meditative passages to the urgent, staccato rhythm of Ahab’s monologues and action sequences.